TPACK y COVID 19: una revisión sistemática de la literatura (Memorias Sifored - Encuentros Educación UAN, 2022)
The objective of this study was to determine the main findings reported worldwide in relation to TPACK during the isolations generated by the spread of Covid-19. A search was performed in the Scopus database and inclusion and exclusion criteria were applied to the results, after which 10 articles were selected for review. The key words that determined the search were TPACK and Covid-19. The main findings were categorized in reference to TPACK levels, professional development courses and teachers' gender and experience. There was a predominance of research of Asian origin and a high percentage agreed that the change in the way teaching and learning processes were carried out during the pandemic was sudden and took teachers with little preparation.
Keywords: TPACK; Covid-19; Virtual Education; teachers